Relationship Of Information Exposure And Covid-19 Prevention Towards Stress Levels - Rebu, Rikardus Eka Deseley; Asmarani, Fajarina Lathu; Muflih, Muflih (Universitas Respati Yogyakarta, 2020)
Almost part of the community is in uncertainty and has received a lot of information about COVID-19 through various media that cannot be justified. During this pandemic, the community was also required to take COVID-19 preventive measures. This condition unconsciously creates panic and stress in the community. The aim this research is to analysis of the relationship between information exposure and COVID-19 prevention measures to stress levels is known. This research used analytical observational method with cross-sectional design. The research subjects were citizens in residents of household 03 in Seniung Jaya Village, Paser Belengkong District, Paser Regency, East Kalimantan Province, Indonesia.. The sample in this study amounted to 125 residents. The bivariate analysis of the data used in this study was the Fisher’ exact Test. The result showed that the characteristics of the respondents are mostly 20-29 years old, namely entering early adulthood. Most of the respondents' occupations are private and farmers. The level of exposure to COVID-19 information is low and COVID-19 precautions are good. The p-value is 0.214 and 0.588. The conclusion of this study is that there is no significant relationship relationship between exposure to information and COVID-19 prevention measures on stress levels.